A fuzzy programming approach to neutrosophic complex nonlinear programming problem of real functions in complex variables via lexicographic order - Khalifa, Hamiden Abd El-Wahed; Kumar, Pavan (Opsearch, 2022)
In this article, a complex nonlinear programming problem with objective function coefficients characterized by neutrosophic numbers and fuzzy inequalities constraints is considered. Using the score function definition, the model is converted into the corresponding crisp model with fuzzy inequalities, which can be further partitioned into two real sub-models based on the Lexicographic order. A fuzzy programming approach is applied to each sub-problem by introducing the membership functions. Linear membership function is used to obtain optimal compromise solution. A numerical experimentation is performed for the sake of the suggested approach for illustration.